Ecological Cognitive Analysis of Chinese Harmonious Discourse - Chun-ling, Zou (Frontiers in Psychology, 2021)
This paper is concerned with cognitively and consciously enacting a new dialectical opposite-unity approach into Chinese harmonious discourse(CHD) analysis in an ecological perspective, which contributes to converting an antagonistic thinking between human and nature into an ecological harmonious one cultivated into an unconscious state. The method applied is primarily the theoretical analysis and interpretation, due to the newness of this subject and the lack of corpus data. The motivation of this paper is evoked by the discovery of various cognition dissonances and insufficiencies with the academic development of a newly-born ecolinguistics. On a micro or specified level, this paper presents a cutting-edge example of an ecologically cognitive approach to the analysis of CHD, based on Chinese dialectical opposite-unity philosophy, for the purpose of constructing a higher level cognition mechanism into a habitually unconscious thinking state. Such mechanism has its practical significance in devoting to: alleviating the ecological crisis by a change in ways of thinking, to mediating cognitive dissonance brought about by the crisis, and to improving the one-sided cognition deficiency brought about by ways of antagonistic thinking in order to maintain the ecological harmony. The theoretical significance lies in it demonstrating the cognitive process about how the unconscious ecological harmony cognition is cultivated by the conscious operational opposite-unity cognition procedure, with the ultimate purpose to achieve and maintain a real ecological harmony, under the cross-cultural background.